Pathogenesis and treatment of chronic rhinosinusitis from the perspective of sinonasal epithelial dysfunction - He, Yuanqiong; Fu, Yijie; Wu, Yuqi; Zhu, Tianmin; Li, Hui (Frontiers in Medicine, 2023)
Chronic rhinosinusitis (CRS) is a clinical syndrome characterized by long-term mucosal inflammation of the nasal cavity and sinuses. For its high heterogeneity, the pathogenesis of CRS is still unclear. More and more studies focus on sinonasal epithelium. In the recent years, there has been a quantum leap in the consciousness of sinonasal epithelium, from an inert mechanical barrier to an active functional organ. Undoubtedly, epithelial dysfunction plays a vital role in the occurrence and development of this disease. Impaired MCC and abnormal sinonasal epithelial barrier are usually considered as the direct causes of CRS. Epithelial-derived bioactive substances such as cytokines, exosomes and complements, have been well established as the important participants in innate and adaptive immunity and contribute to the pathophysiological alterations of CRS. The phenomena of EMT and autophage observed in CRS offer a new insight into the pathogenesis of this disease. Current and developing treatments targeting the disorder of sinonasal epithelium, to a degree, help to relieve the main symptoms of CRS. Complete and normal epithelium is fundamental for maintaining the homeostasis in nasal and paranasal sinuses. Here, we investigate the multiple aspects of sinonasal epithelium and confirmed the contributions of epithelial dysfunction to CRS pathogenesis. Our review provides an evidence for the necessity to study in-depth the pathophysiological alterations of this disease and developing the novel epithelial-targeted alternatives. In this article, we present the current awareness of the contribution of sinonasal epithelium lesions to CRS pathogenesis and explore some current and developing therapeutic options targeting the sinonasal epithelium.